Caretaker Cabinets in Belgium: A New Measurement and Typology - Dandoy, Régis; Terrière, Lorenzo (Politics of the Low Countries, 2025)
Belgium is probably the world’s best known case of where caretaker governments reside. Yet a clear scholarly definition and measurement of this concept is missing. Based on a detailed analysis of the Belgian federal cabinets, this research note explores the main characteristics and measures the length of the various caretaker periods. We find that Belgium was governed for no less than 1,485 days by a caretaker government between 2007 and 2020, which equals more than four full calendar years. This research note also presents a novel typology of caretaker periods based on the institutional and political practice within the Belgian legislative and executive branches. This typology can be used to assess caretaker periods at other levels of government as well as in other countries in order to improve our understanding of the many ‘faces’ that a caretaker government can take on.